Dzienniczki uczących się jako narzędzie badawcze – próba oceny - Nerlicki, Krzysztof (Neofilolog, 2009)
The present study focuses on the use of learner diaries as an empirical tool. We discuss the pros and cons of this approach. Diary studies are classified as methods in exploratory-interpretive research. Diaries can help investigate language learner behaviors, encourage student self-assessment and explore how the language learning processes progress. The most problematic methodological aspects are the following: data collection, limitations of learners’ reflections and limited generabilizity.